Implementasi Konsep Altarea dalam Perancangan Interior Pusat Eksplorasi Potensi Lokal di Kota Semarang - Elvina Kurniawati Haryanto; Diana Thamrin; Linggajaya Suryanata (Intra, 2019)
Semarang has a lot of potentials that continue to be developed by the government. Semarang is located in route that is often travelled by tourist from East Java and West Java. The design of this Semarang Potential Exploration Centre has objectives for accommodating tourist to learn about the potentials of Semarang in entertaining way while helping the livelihood of local communities, micro small and medium enterprises through workshops or exhibitions. The method used is design thinking with stages of Understanding, Observation, Point of View, Ideate, Prototype, and Test. The final design is an implementation of concept “the fun of exploring Semarang” supported by technologies in order to attract more visitors interest in Semarang without losing its locality.